Corporate negative publicity – the role of cause related marketing - Vyravene, Revadee; Rabbanee, Fazlul (Elsevier, 2016)
This paper examines the effects of cause-related marketing (CrM) strategies on consumers' moral judgement and purchase behaviour in the context of experiencing substantial corporate negative publicity. Data for the study were collected from 343 respondents through mall intercept technique from two large shopping malls of Australia. Quasi-experimental design technique was adopted for the study, where the participants chose one particular cause out of two (ongoing conventional cause vs sudden disaster due to garment factory collapse in Bangladesh). The findings revealed that 56% of the respondents supported the sudden cause and are willing to pay (WTP) more for the betterment of the garment workers' living condition. The findings further indicated that CrM variables such as cause–brand fit, cause familiarity and cause importance influence consumers' moral judgement towards the CrM campaigns, which eventually influence them to pay additional money for the product. The multi-group moderation and mediation tests offer interesting theoretical and managerial insights.